QUASI-MODALS IN BRITISH AND AMERICAN ENGLISH - Oktavianti, Ikmi Nur (Jurnal Bahasa Lingua Scientia, 2016)
In daily use of language, speakers need to use certain linguistic units to convey messages to the interlocutors. To assert non-factual condition, there are modality markers as parts of language elements. English grammar marks the modality concept by means of modal verbs, adverbs, adjective, conditional sentence, and the like. Regarding modal verbs, one of them is quasi-modal. This paper then examines quasi-modals in English. However, talking about English cannot be separated from its regional varieties. This research thus aims to describe the differences of quasi-modals in British English and American English. To complete the research, it attempts to reveal the factors triggering the differences.